2011
DOI: 10.2147/ijgm.s17156
|View full text |Cite
|
Sign up to set email alerts
|

Suicide ideation, plans, and attempts among general practice patients with chronic health conditions in Puerto Rico

Abstract: Background:Little is known about suicidal ideation among general practice patients in Puerto Rico. In this study we examined the rates, severity, and correlates of suicidal ideation, plans, and attempts among general practice patients with chronic illnesses. This is important in targeting appropriate interventions and management approaches to minimize and prevent suicide.Methods:We screened patients with chronic physical conditions at general practices. Suicidal ideation was assessed with the suicidality modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
(34 reference statements)
1
11
3
1
Order By: Relevance
“…However, previous findings regarding the association between gender and suicide attempts have been inconsistent; some studies found that females have a greater risk for lifetime suicide attempts compared with males (5,6,8,10), while others found that gender was not associated with suicide attempts (7,(11)(12)(13)15). Until now, the association between gender and suicide attempts had not been determined in Korea, although gender was not significantly associated with suicide attempts in this study (data not shown).…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…However, previous findings regarding the association between gender and suicide attempts have been inconsistent; some studies found that females have a greater risk for lifetime suicide attempts compared with males (5,6,8,10), while others found that gender was not associated with suicide attempts (7,(11)(12)(13)15). Until now, the association between gender and suicide attempts had not been determined in Korea, although gender was not significantly associated with suicide attempts in this study (data not shown).…”
Section: Discussioncontrasting
confidence: 67%
“…However, other studies have found that marital status is not associated with suicide attempts (7,11,15). In the present study, males who were widowed, divorced, or separated participants had a higher risk for suicide attempts than that of male participants who were married, whereas the risk was lower risk for females.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations